The riddle of the world a reconsideration of Schopenhauer's philosophy - Hannan, Barbara (Oxford : Oxford University Press, 2009)
This text is an introduction to the philosophy of Arthur Schopenhauer, written in a lively, personal style. Hannan emphasizes the peculiar inconsistencies and tensions in Schopenhauer's thought.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Schopenhauer, Arthur, -- 1788-1860.